Zapowiedź repertuarowa – analiza gatunku na podstawie tekstów ze stron internetowych teatrów dramatycznych i muzycznych - Smól, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article constitutes an attempt at a genological analysis of repertoire previews. The research material comes from the websites of dramatic and musical theatres. The methodological foundation of the study is based on findings from linguistic genre studies. The introductory section provides a description of the theatrical teaser as a media genre blending elements of informational and promotional content. Its primary purpose is to capture the audience’s attention, spark their interest and prompt action – in this case, purchasing tickets for the upcoming performance. The structural framework of the analysis is based on the composition of the examined texts. Key components include: framing elements (such as the title, list of artists involved in the production and photographs), a synopsis of the upcoming performance, a description of the historical background, an overview of the creators’ achievements, quotations from their statements and carefully-selected review excerpts. The analysis is centred on the structure of the texts, with individual segments constituting the theatre teaser also examined from pragmatic, stylistic and rhetorical perspectives. The marketing objective behind theatre announcements leads their creators to produce messages full of paradoxes, balancing between informing, intriguing and persuading, between a fixed form and originality of expression. These announcements draw on traditional models (closely resembling journalistic teasers), while simultaneously exploiting the potential of the new medium.